2017
DOI: 10.1002/chem.201702251
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Quinoline‐Class Antimalarials to Identify Fundamental Physicochemical Properties of Beta‐Hematin Crystal Growth Inhibitors

Abstract: A versatile approach to control crystallization involves the use of modifiers, which are additives that interact with crystal surfaces and alter their growth rates. Elucidating a modifier's binding specificity to anisotropic crystal surfaces is a ubiquitous challenge that is critical to their design. In this study, we select hematin, a byproduct of malaria parasites, as a model system to examine the complementarity of modifiers (i.e., antimalarial drugs) to β-hematin crystal surfaces. We divide two antimalaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Further studies revealed that chloroquine (CQ) binds preferentially to the {001} crystal surfaces, whereas amodiaquine (AQ) binds nonpreferentially to both the {001} and {010} surfaces. 9 Both CQ and AQ are able to form 2 : 1 FePPIX : drug complexes, 8 but the formation of such complexes is not necessarily correlated with the ability to inhibit β-haematin crystal growth. More generally, published experimental studies have not yet been able to resolve the question of whether free drug molecules or molecular drug-haem complexes are responsible for crystal poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies revealed that chloroquine (CQ) binds preferentially to the {001} crystal surfaces, whereas amodiaquine (AQ) binds nonpreferentially to both the {001} and {010} surfaces. 9 Both CQ and AQ are able to form 2 : 1 FePPIX : drug complexes, 8 but the formation of such complexes is not necessarily correlated with the ability to inhibit β-haematin crystal growth. More generally, published experimental studies have not yet been able to resolve the question of whether free drug molecules or molecular drug-haem complexes are responsible for crystal poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Other hybrid-based drugs have displayed potency equal or superior to parental drug and antimalarial quinolines of reference, such as amodiaquine and chloroquine [13,26]. Consistent with this notion and based on a model of structural determinants for 7-chloroquinolines inhibiting β-hematin formation [42], a plausible reason for increased inhibitory potency of hybrid for β-hematin crystal formation is a combination of binding affinity of 7-chloroquinoline component for ferric Fe-PPIX and the chemical linker playing a role as a side chain by assisting further binding property. To understand the reason for the 163A hybrid to inhibit β-hematin formation in an oxidizing condition, measurement of the association constant for ferric hematin (log K) was determined.…”
Section: Dual Role On the Heme Detoxification Processmentioning
confidence: 69%
“…This result indicates that binding of 163A to ferric hemin is weaker than to chloroquine. Literature has shown the aminoalkyl side chain of chloroquine is essential for its binding to Fe-PPIX [42] and based on this, a formal possibility is that the chemical linker of the 163A hybrid may not reproduce an optimal binding affinity as observed for chloroquine. Furthermore, the speciation of hematin-drug complexation observed in titration experiments may not be the same as observed for β-hematin assays, justifying the increased potency of hybrid for inhibiting β-hematin formation than chloroquine.…”
Section: Dual Role On the Heme Detoxification Processmentioning
confidence: 99%
“…Assuming that only the 7‐chloroquinoline part of hybrid compound 14 is responsible for the β‐hematin inhibitory properties, the observation that compound 14 is as potent as chloroquine is explained by the fact that the 7‐chloroquinoline moiety in the hybrid compound can adopt different conformations and orientations, in part greatly influenced by the linker group. While this kind of potency enhancement against β‐hematin formation has been observed for quinoline derivatives, it has not been demonstrated in experimental malaria. Here, we introduce the notion that the potency enhancement of hybrid compound 14 against β‐hematin correlates well with its efficacy in impairing parasite hemozoin in experimental malaria.…”
Section: Resultsmentioning
confidence: 99%